Inclusion of pupils with hearing difficulties in mainstream educational institutions: A comparative case study of a public and private school in the UAE - MOSHARBAK, NOORA ABDULLA (2017)
The United Arab Emirates (UAE) is one of the countries to have acknowledged international community standards in an effort to reform education. The need for inclusive education was recognized by the Ministry of Education (MoE) in 1979, even though little attempts were made to incorporate the concept of inclusion into the regulatory frameworks of the country until 2006. The present investigation builds on a holistic approach to a successful inclusion in the short-term using a comparative case study of one public and one private educational institution. In addition, it focuses on the criteria of including children with hearing impairments. The study has as part of its objective to investigate the attitudes of teachers and parents towards the inclusion of children with hearing impairment, to investigate the perceived level of resource adequacy towards inclusion, and to investigate the perceived level of curricula adequacy towards inclusion. The study adopts a highly versatile a qualitative and quantitative (mixed research) approach. Results generally indicate that more positive results exist in public institutions as opposed to private institutions. This is true in all areas of attitudes, perceived results and perceived curricula adequacy. It is recommended that future investigations focus on a larger pool of institutions and disabilities. Future investigations can also focus on the long-term success criteria for inclusive education. It is also recommended that UAE adopts a continuous improvement approach to the adoption and development of inclusive education. A higher benchmark may be set in order to push private institutions to install adequate resources and curricula for inclusion. In the area of attitudinal change, the government must step up public education in this area to realize some improvement in attitude towards inclusion.